(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This article analyzes the role of healthcare facilities in urban planning, their location, and their impact on infrastructure. The author highlights the importance of population needs, the transportation system, ecological factors, and the principle of territorial equality in the placement of medical institutions. The article explores ways to efficiently organize healthcare services in modern urban planning using GIS technologies and smart city approaches. It also covers the impact of ecological sustainability and green spaces on the efficiency of medical facilities.